2011
DOI: 10.1002/ejic.201100823
|View full text |Cite
|
Sign up to set email alerts
|

A Coordination Chemistry Study of Solvated Thorium(IV) Ions in Two Oxygen‐Donor Solvents

Abstract: The structures of the dimethyl sulfoxide (dmso) and N,N′‐dimethylpropyleneurea (dmpu) solvated thorium(IV) ions have been studied in solution by extended X‐ray absorption fine structure (EXAFS), and the structure of the solid oxonium bis[nonakis(κO‐dimethyl sulfoxide)]thorium(IV) trifluoromethanesulfonate dihydrate, (H3O)[Th((CH3)2SO)9]2(CF3SO3)9·2H2O (1) has been determined by single‐crystal X‐ray diffraction and EXAFS. Compound 1 was crystallized by evaporating a saturated dmso solution. It consists of two i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
5
8
0
Order By: Relevance
“…2.45 Å, but the coordination numbers are 6, 8, 9 and 9, respectively, 63 66 and for the dmso-solvated sodium, calcium and europium( iii ) and thorium( iv ) ions with bond distances of 2.43, 2.36, 2.40 and 2.47 Å, the coordination numbers are 6, 7, 8 and 9, respectively. 31 , 63 , 67 , 68 …”
Section: Discussionmentioning
confidence: 99%
“…2.45 Å, but the coordination numbers are 6, 8, 9 and 9, respectively, 63 66 and for the dmso-solvated sodium, calcium and europium( iii ) and thorium( iv ) ions with bond distances of 2.43, 2.36, 2.40 and 2.47 Å, the coordination numbers are 6, 7, 8 and 9, respectively. 31 , 63 , 67 , 68 …”
Section: Discussionmentioning
confidence: 99%
“…Organic ligands are obviously represented by a major number of examples. Thus, the structure of the dimethyl sulfoxide (DMSO)-solvated thorium(IV) ions was studied in solution by EXAFS) and the structure of the solid oxonium bis [nonakis(κ O -dimethyl sulfoxide)]thorium(IV) trifluoromethane-sulfonate dihydrate, (H 3 O)[Th((CH 3 ) 2 SO) 9 ] 2 (CF 3 SO 3 ) 9 ·2H 2 O was determined [17]. It consists of two individual nonakis(κ- O -dimethyl sulfoxide)thorium(IV) units, both of which have a tricapped trigonal prismatic configuration, as also found earlier in nonakis(dimethyl sulfoxide)thorium(IV) perchlorate.…”
Section: Part a Actinides Chemistrymentioning
confidence: 99%
“…49 We should note that in the case of La 3+ , the information on structure and coordination numbers obtained from the cluster growing approach were very similar to what was then obtained in liquid phase and they turned out to be crucial in developing a general force field for molecular dynamics studies. The appropriateness of the cluster model approach is further assessed by the fact that in this kind of systems, as observed by Persson and co-workers, the crystal and liquid EXAFS signals are very similar; 34,47 this means that the main features of the metal−DMSO complexation are not modified by a change of bulk phase thus suggesting that the intrinsic ion−solvent interaction is strong enough to determine the solvation structure. This is the main reason why studying clusters in the gas phase allows us in these cases to obtain a realistic picture of the solvation of these ions even if the liquid environmental effect is neglected.…”
Section: ■ Introductionmentioning
confidence: 97%
“…30 We have focused our attention on Th 4+ solvation because it represents a good model to understand solvation of light bare actinoid cations in oxygen donor solvents. This choice was additionally motivated by the fact that information on coordination of Th 4+ in two oxygen donor solvents (dimethyl sulfoxide (DMSO) and dimethylpropylurea (DMPU)) have been recently determined experimentally in liquid phase by Torapava et al 34 For DMSO, the same authors 34 also reported X-ray structures and extended X-ray absorption fine structure (EXAFS) in solid state. Recently, we have shown that the use of an approach based on the study of small clusters of solvent molecules is extremely useful and we have used it to gather information on the DMSO structure around La 3+ .…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation